Pengaruh Social Media Marketing, Influencer Marketing, Online Customer Rating Dan Ease Of Purchase Access Terhadap Keputusan Pembelian Pada Umayumcha Malang - Sandi, Dian Kharisma; Rizal, Muhammad; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the influence of Social Media Marketing, Influencer Marketing, Online Customer Rating, and Ease of Purchase Access on purchasing decisions at Umayumcha Malang. The research uses a quantitative approach with an explanatory research method. Data were collected through an online questionnaire involving 105 respondents who are customers of Umayumcha. The results show that both partially and simultaneously, the four independent variables significantly influence purchasing decisions. Social Media Marketing and Influencer Marketing are proven effective in increasing buying interest, while Online Customer Rating and ease of purchase access further strengthen consumer decisions. These findings are expected to serve as a reference for digital marketing strategies, especially in the culinary business. Keywords: Social Media Marketing, Influencer Marketing, Online Customer Rating, Ease of Purchase Access, Purchasing Decision.